FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM PADA UNIVERSITAS BENGKULU - Husaini, Husaini; Aisyah, Siti; Verawati, Hasrini (JURNAL FAIRNESS, 2015)
This study aims to examine and obtain empirical evidence about the factors that influence the effectiveness of financial management. This research is motivated by the fact that the financial management of public service agencies that applied at the University of Bengkulu is not effective, because a number of phenomena which appear among others: the mindset (mindset), patterns of attitudes and patterns of management actions in the bureaucracy still long before BLU is rigid (inflexible) and not flexible in financial management, and management tend to be transparent as well as with the process of disbursement and financial reporting has not shown the expected public accountability.The variables to be tested in this study of human resources, the utilization of information technology, systems of internal control and governance of the effectiveness of financial management This research was conducted by giving questionnaires to financial managers University of Bengkulu that have been based on the ease of obtaining the sample. The results of this study are quality human resources and internal control system does not affect the effectiveness of financial management. As for the utilization of research results and governance of information technology or a significant positive impact on the effectiveness of the financial management of public service agencies at the University of Bengkulu